The Relationship between The Use of Peek a Book Hair Colour and The Level of Confidence in UNESA Cosmetology Students Class of 2022 - Afifah Maulidiyatul Ula Ula; Biyan Yesi Wilujeng; Mutimmatul Faidah; Sri Usodoningtyas (Universitas Negeri Surabaya, 2025)
The Peek-a-Boo coloring technique involves selecting specific parts of the hair, such as the undercoat or around the middle of the hair, which are then given a strikingly different color. One of the coloring that attracts the attention of teenagers is Peek-a-Boo hair coloring, where bright or contrasting shades of color are applied to a portion of the hair to create an interesting effect. This study aims to analyze the effect of Peek-a-Boo hair coloring on the confidence level of cosmetology education students of the class of 2022. The problems raised are how to choose the preferred color in this coloring technique, how to use Peek-a-Boo coloring on student confidence levels and find out the relationship between the use of Peek-a-Boo hair color and the confidence level of makeup students of the 2022 batch. The method used was quantitative correlation involving 40 respondents, where data was collected through a questionnaire regarding color choice and its impact on self-confidence. The results showed that 40% of respondents preferred shade colors (maroon, navy, magenta), while the confidence level of UNESA makeup students of the class of 2022 after using Peek-a-Boo hair dye showed positive results, where students had a high level of confidence after using Peek-a-Boo hair dyeing. Further analysis revealed a significant relationship between color use and confidence levels, with a Pearson correlation of 0.880 (p-value < 0.01) and a coefficient of determination (R²) of 0.768. This study confirms that the color selection in Peek-a-Boo hair coloring not only affects appearance, but also increases student confidence.